2021
DOI: 10.3762/bjoc.17.138
|View full text |Cite
|
Sign up to set email alerts
|

Constrained thermoresponsive polymers – new insights into fundamentals and applications

Abstract: In the last decades, numerous stimuli-responsive polymers have been developed and investigated regarding their switching properties. In particular, thermoresponsive polymers, which form a miscibility gap with the ambient solvent with a lower or upper critical demixing point depending on the temperature, have been intensively studied in solution. For the application of such polymers in novel sensors, drug delivery systems or as multifunctional coatings, they typically have to be transferred into specific arrang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 380 publications
(545 reference statements)
0
18
0
Order By: Relevance
“…20,56,57 UCST polymer systems bring an additional advantage of using temperature as a trigger to control capture and release of small molecules and drugs. [58][59][60] Many of such systems, however, include block copolymer micelles (BCMs) which require additional crosslinking to suppress their disintegration above UCST in solutions. 58 In contrast, UCST star polymers are unimolecular nanocontainers which do not disintegrate at an increased temperature.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
See 1 more Smart Citation
“…20,56,57 UCST polymer systems bring an additional advantage of using temperature as a trigger to control capture and release of small molecules and drugs. [58][59][60] Many of such systems, however, include block copolymer micelles (BCMs) which require additional crosslinking to suppress their disintegration above UCST in solutions. 58 In contrast, UCST star polymers are unimolecular nanocontainers which do not disintegrate at an increased temperature.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…[58][59][60] Many of such systems, however, include block copolymer micelles (BCMs) which require additional crosslinking to suppress their disintegration above UCST in solutions. 58 In contrast, UCST star polymers are unimolecular nanocontainers which do not disintegrate at an increased temperature. To explore the ability of UCST linear and star PUEMs to trap and release drug molecules, we used proflavine hydrochloride (Fig.…”
Section: Polymer Chemistry Papermentioning
confidence: 99%
“…While it has already been shown for well-known LCST polymers such as PNiPAAm that the polymer architecture has a major influence on the thermoresponsive transition of the brushes, 39−42 this aspect still remains largely unexplored for polymers with an UCST-type behavior. 10 To the best of our knowledge, there has not been any study so far that systematically analyses the influence of grafting density on the UCST-type transition of a polymer brush. Although interest in polymers with UCST-type behavior is strongly increasing, 43 it was pointed out in a review article recently that there is still only a very limited number of polymers known to exhibit UCST-type behavior in aqueous solution yet.…”
Section: Introductionmentioning
confidence: 99%
“…The design of hollow polymer capsules comprising a stimuli-responsive polymer shell has enabled major progress to remotely control the release of core-encapsulated payloads. , Extensive studies on temperature-responsive polymers operating in water have been reported, likely because a temperature shift by a few °C is a mild, nontoxic, additive-free trigger . These polymers are characterized either by a lower or upper critical solution temperature (LCST or UCST). , LCST polymer chains are switching from hydrophilic, soluble coils to hydrophobic collapsed globules upon heating above the LCST. UCST polymer chains exhibit the opposite behavior and are water-soluble above the UCST. , …”
mentioning
confidence: 99%
“…The main drawback of these systems is the sensitivity of thermal responses to environmental features . Their cloud point is, in practice, tuned by adjusting the polymer structure (composition, chain length, end-groups), but minor chemical degradation or effect of pH or salts made it a challenging task. ,, Acidic or salt impurities may, for instance, shift the working temperature by >10 °C. , The cloud point of poly­( N -acryloylglycinamide), one of the earliest nonionic copolymers with chemically adjustable properties, shifts from 20 °C to above 100 °C when about 0.2 mol % of the monomer is hydrolyzed . Interactions with the drug cargo can also perturb the thermal response. , …”
mentioning
confidence: 99%